Astrocyte‐selective STAT3 knockdown rescues methamphetamine withdrawal‐disrupted spatial memory in mice via restoring the astrocytic capacity of glutamate clearance in dCA1. Issue 10 (10th June 2021) - Shi, Pengbo; Li, Zhaosu; He, Teng; Li, Nanqin; Xu, Xing; Yu, Peiyao; Lu, Xue; Nie, Jiaxun; Liu, Dekang; Cai, Qinglong; Guan, Yun; Ge, Feifei; et al.
Abstract: Methamphetamine (METH) is a common abused drug. METH‐triggered glutamate (Glu) levels in dorsal CA1 (dCA1) could partially explain the etiology of METH‐caused abnormal memory, but the synaptic mechanism remains unclear. Here, we found that METH withdrawal disrupted spatial memory in mice, accompanied by the increases in Glu levels and postsynaptic neuronal activities at dCA1 synapses. METH withdrawal weakened the capacity of Glu clearance in astrocytes, as indicated by increasing the A1‐like astrocytes and phosphorylated signal transducer and activator of transcription 3 (p‐STAT3), decreasing the Glu transporter 1(GLT‐1, also known as EAAT2 or SLC1A2), Glu‐aspartate‐transporter (GLAST also known as EAAT1 or SLC1A3) and astrocytic glutamine synthase (GS), but failed to affect the presynaptic Glu release from dCA3 within dCA1. Moreover, we identified that in vitro A1‐like astrocytes exhibited an increased STAT3 activation and the impaired capacity of Glu clearance. Most importantly, selective knockdown of astrocytic STAT3 in vivo in dCA1 restored the astrocytic capacity of Glu clearance, normalized Glu levels at dCA1 synapses, and finally rescued METH withdrawal‐disrupted spatial memory in mice. Thus, astrocytic Glu clearance system, especially STAT3, serves as a novel target for future therapies against METH neurotoxicity. MAIN POINTS: The weakened astrocytes‐dependent Glu clearance by METH withdrawal contributes to the memory deficits in mice. In vivo STAT3 knockdown in dCA1 astrocytes rescues the disrupted spatial memory by restoring astrocytic capacity of Glu clearance in METH withdrawal mice.